d Perbandingan Konstruksi Beton Risha dan Konvensional: Tinjauan Biaya dan Waktu - Sulistiana, Putu Didik; Agustini, Ni Komang Ayu; Setiawan, I Made Edi (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
The RISHA innovation (Simple Healthy Instant House) is a variation of precast concrete created by the Center for Research and Development (Puslitbang) for Settlements, Ministry of Public Works and Public Housing, which was released on December 20 2004. The aim of this research is to determine the comparison of building construction with technology. RISHA concrete and conventional concrete from the aspect of calculating project costs and calculating project duration. The approach in this research uses a type of research in the form of a literature study or literature study. The results of research comparing building construction using RISHA concrete technology and conventional concrete showed that the average cost difference was 7.96%, and the average difference in duration was 30.10%, superior to RISHA concrete technology.